Measuring the Gap Between the Syrian Accounting Qualifications and the International Accounting Education Based on IES 2 and IES 3 - Al-Taweel, Laila M (The Economics and Finance Letters, 2015)
The accountancy profession is responsible for providing, auditing, and analyzing financial and non-financial information needs of a broad range of decision makers. The accountancy profession’s ability to satisfy users’ information needs and also to testify this information protects the public interest and contributes to the economy. Since accountants are providers, auditors, and analysts of information, they significantly impact the business environment, and the overall society. Therefore, accountants’ qualifications and skills need to be upgraded and evaluated periodically. This upgrading and evaluation need some sort of references or standards. This paper measures the gap between the Syrian accounting qualifications (curricula and skills) and the international accounting education based on International Education Standards, specifically on IES 2 and IES 3 as a benchmark. Results indicate a large gap in terms of IES 2, and a medium gap in terms of IES 3.